Splaying a search tree in preorder takes linear time - R. Chaudhuri; H. Höft (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove that if the nodes of an arbitrary n-node binary search tree T are splayed in the preorder sequence of T then the total time is O(n). This is a special case of the splay tree traversal conjecture of Sleator and Tarjan.